TINDAKAN PENGGELAPAN PAJAK TERHADAP MONEY ETHICS DAN TEKNOLOGI INFORMASI YANG DIMODERAI RELIGIUSITAS - Suprihatin, Neneng Sri (Universitas Muhammadiyah Palembang, 2022)
This study aims to empirically examine the effect of money ethics and tax information technology on tax evasion moderated by religiosity. This researcher uses associative research methods while the type of research used is quantitative research. The population in this study are individual and corporate taxpayers in Serang City (UMKM). The sample in this study was determined by the Probability Sampling method with Determination of the number of samples using the Slovin Formula and the data were collected through questionnaires with a total of 275 respondents, and the questionnaire could only be processed with 163 respondents, the rest were filled in or not returned. The data analysis method uses SPSS.The results of this study indicate that 1) Money ethics influences tax evasion. 2) Tax information technology has no effect on tax evasion. 3) Religiosity influences towards tax evasion. Whereas 4) The variable of religiosity is proven unable to moderate the relationship of money ethics to tax evasion. And 5) The variable of religiosity is proven to be able to moderate the relationship of taxation information technology to tax evasion